Theory of Interaction in Law Enforcement Administration - Hrechanyik, Serhii; Tereschuk, Halyna; Mamchur, Lidiia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the problem – research of origin and development of scientific positions which determine maintenance of scientific category «interaction»in the general theory of management and management law enforcement authorities